ABOUT THE POLICY OF THE EMPIRE ADMINISTRATION IN TURKESTAN ON REGARDING THE WAQF LANDS (American Journal of Research in Humanities and Social Sciences, 2024)
This article presents the author’s opinion on the colonial policy of the imperial government regarding waqf lands in Turkestan using the example of the territory of the Syrdarya region. The source base for the researcher’s research in justifying the content of the space was a number of scientific literature and archival documents.